The use and domestication of Theobroma cacao during the mid-Holocene in the upper Amazon. Issue 12 (December 2018) - Zarrillo, Sonia; Gaikwad, Nilesh; Lanaud, Claire; Powis, Terry; Viot, Christopher; Lesur, Isabelle; Fouet, Olivier; Argout, Xavier; Guichoux, Erwan; Salin, Franck; Solorzano, Rey; Bouchez, Olivier; et al.
Abstract Cacao (Theobroma cacao L.) is an important economic crop, yet studies of its domestication history and early uses are limited. Traditionally, cacao is thought to have been first domesticated in Mesoamerica. However, genomic research shows thatT. cacao 's greatest diversity is in the upper Amazon region of northwest South America, pointing to this region as its centre of origin. Here, we report cacao use identified by three independent lines of archaeological evidence—cacao starch grains, absorbed theobromine residues and ancient DNA—dating from approximately 5, 300 years ago recovered from the Santa Ana-La Florida (SALF) site in southeast Ecuador. To our knowledge, these findings constitute the earliest evidence ofT. cacao use in the Americas and the first unequivocal archaeological example of its pre-Columbian use in South America. They also reveal the upper Amazon region as the oldest centre of cacao domestication yet identified. Evidence from starch grains, theobromine residues and ancient DNA demonstrate cacao use in the upper Amazon circa 5, 300 years ago. This is earlier than previous evidence for cacao domestication in Mesoamerica.